2016
DOI: 10.1039/c6cp01578f
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational solvatochromism of nitrile infrared probes: beyond the vibrational Stark dipole approach

Abstract: Systematic probing of local environments around biopolymers is important for understanding their functions. Therefore, there has been growing interest in in situ measurements of molecular granularity and heterogeneity through the systematic analysis of vibrational frequency shifts of carbonyl and nitrile infrared probes by vibrational Stark dipole theory. However, here we show that the nitrile vibrational frequency shift induced by its interaction with the surrounding molecules cannot be solely described by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 87 publications
7
136
0
Order By: Relevance
“…In this approach, the vibrational frequencies and transition dipole moments are calculated from a property easily obtained from an MD trajectory, typically an electric field component exerted on the molecule by the solvent. It has been previously observed that this approach fails for alkyl nitriles in various solvents 7,[41][42][43] (where the frequency shift is very sensitive to charge transfer effects) as well as for anionic solutes in water clusters where more complex approaches have been proposed for SCN . 42,44,45 However, we have found that such a relationship can be obtained for SeCN in aqueous solutions.…”
Section: B Spectroscopic Modeling Via An Empirical Frequency Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…In this approach, the vibrational frequencies and transition dipole moments are calculated from a property easily obtained from an MD trajectory, typically an electric field component exerted on the molecule by the solvent. It has been previously observed that this approach fails for alkyl nitriles in various solvents 7,[41][42][43] (where the frequency shift is very sensitive to charge transfer effects) as well as for anionic solutes in water clusters where more complex approaches have been proposed for SCN . 42,44,45 However, we have found that such a relationship can be obtained for SeCN in aqueous solutions.…”
Section: B Spectroscopic Modeling Via An Empirical Frequency Mapmentioning
confidence: 99%
“…It has been previously observed that this approach fails for alkyl nitriles in various solvents 7,[41][42][43] (where the frequency shift is very sensitive to charge transfer effects) as well as for anionic solutes in water clusters where more complex approaches have been proposed for SCN . 42,44,45 However, we have found that such a relationship can be obtained for SeCN in aqueous solutions. We calculated the anharmonic vibrational frequency of the CN stretch in SeCN in water for 500 configurations sampled every 4 ps from one of the 4 ns MD trajectories described above.…”
Section: B Spectroscopic Modeling Via An Empirical Frequency Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in practice it is not always easy and straightforward, or even possible, to tell whether an IR probe is engaged in any hydrogen-bonding (H-bonding) interactions based on its frequency alone. 1517 Herein, we show, using 4-cyanoindole (4-CI) and cyclopentanone (CP) as examples, that for an oscillator exhibiting Fermi resonance, the underlying vibrational coupling constant is a robust and convenient indicator of its H-bonding status.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed to aid in spectral interpretation, including characterization of the temperature-dependence, 26 comparison with NMR chemical shifts, 45 and a range of approaches based on theoretical modelling. 27,4648 However, these approaches are all challenging with many proteins due to protein size or stability. The data presented here suggest that CNSePhe could provide a less ambiguous probe of solvation, with the observation of short lifetimes indicative of H-bonding, and conversely, longer lifetimes indicative of the absence of H-bonds.…”
Section: Resultsmentioning
confidence: 99%